Development of a Healthy Lifestyle Assessment Toolkit for the General Public - Reis, Flávio; Sá-Moura, Bebiana; Guardado, Diana; Couceiro, Patrícia; Catarino, Luis; Mota-Pinto, Anabela; Veríssimo, Manuel T.; Teixeira, Ana Maria; Ferreira, Pedro L.; Lima, Margarida P.; Palavra, Filipe; Rama, Luis; et al. (Frontiers in Medicine, 2019)
The prevalence of age-related non-communicable chronic diseases has increased worldwide, being the leading causes of morbidity and death in many world regions, including in Europe. Innovative models and strategies focused on preventive care, including early identification of risk factors underlying disease onset and progression, and proper modification of lifestyle habits and behaviors, might contribute to promote quality of life, healthy living and active ageing. Healthy Lifestyle Innovative Quarters for Cities and Citizens (HeaLIQs4cities) is an EIT Health-funded project aiming to engage, empower and educate citizens towards healthy lifestyles. One of the major objectives of this project was to develop a toolkit for a rapid and informal assessment of healthy lifestyles, to be used at different levels of care pathways, including in informal public environments. In this paper, we describe the methodology underlying the development of the toolkit, which resulted from the collaboration of an interdisciplinary focus group of academic experts, from medicine, sport sciences, psychology, health economics and innovative technologies applied to health. The following eight components were included in the toolkit: 1) anthropometric assessment and cardiometabolic parameters; 2) physical activity and exercise; 3) wellbeing, social cohesion and functional independence; 4) nutrition; 5) mental health; 6) smoking, drinking and use of illicit substances; 7) sleep habits/quality; and 8) health and disease. A traffic light rating system indicating the risk score was used (low: green; moderate: yellow; and relevant: orange) for each of the 8 components, together with recommendations for the toolkit users. After completing the reduced version of the toolkit, individuals showing moderate or relevant risk in one or more of the 8 dimensions, were invited to participate in a more detailed assessment (toolkit long version), based on deeper and scientifically validated tools. The toolkit was incorporated in eVida, a web-based platform that focuses on delivering services to personalized health and wellbeing. The validation of the current toolkit has been applied in wide-ranging public events in three different European Regions. Large scale deployment of the toolkit is expected to profit from the Reference Site Collaborative Network of the European Innovation Partnership on Active and Healthy Ageing (EIP on AHA).